Elio [videorecording (Blu-Ray + DVD)] - Jones, Mike, 1971-; Hammer, Mark (Screenwriter); Cho, Julia (Disney / Pixar, 2025)
Elio, a space fanatic with an active imagination, finds himself on a cosmic misadventure where he must form new bonds with alien lifeforms, navigate a crisis of intergalactic proportions and somehow discover who he is truly meant to be.